2008
DOI: 10.1007/s00167-008-0551-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the surgical epicondylar axis and the articular surface of the distal femur: an anatomic study

Abstract: Many authors presented the epicondylar axis as the fixed axis of rotation of the femoral condyles during flexion of the knee. Positioning of the femoral component of a total knee arthroplasty (TKA) based on the epicondyles has been proposed. This work is a critical analysis of this concept. Metallic bodies were inserted at the level of collateral ligament insertions on 16 dried femurs, allowing us to locate the surgical epicondylar axis. The dried femurs were studied using standard radiographs and CT-scan. CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Based on our results, the ICA measured on a CT is not useful in estimating the PCA and thereby gives no information on the distal femoral rotation. Others found lack of correlation between PCA and ICA (called DCA in their study) as well [28].…”
Section: Discussionmentioning
confidence: 81%
“…Based on our results, the ICA measured on a CT is not useful in estimating the PCA and thereby gives no information on the distal femoral rotation. Others found lack of correlation between PCA and ICA (called DCA in their study) as well [28].…”
Section: Discussionmentioning
confidence: 81%
“…Various approaches, including the kinematical analysis, the intra-operative analysis combined with the navigation, and the imaging analysis of the plain radiograph, CT, and magnetic resonance imaging, have been performed [8,14,16,18,21]. However, most of the reports related to the distal femur and the TEA were performed on Caucasian populations, while the present report is mostly restricted to an Asian population.…”
Section: Discussionmentioning
confidence: 95%
“…Difference in the concept may cause the difference between the cylindrical axis and the SEA. In fact, Lustig et al [18] reported that the distances between the SEA and the joint line at 0°, 90°, and mid-range were almost similar, although they pointed out the difference between the cylindrical axis and the SEA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations